Clinical Case of Primary Sclerosing Cholangitis on the Crohn’s Disease of the Upper Gastrointestinal Parts Background - Pazenko, Ekaterina V.; Raikhelson, Karina L.; Kondrashina, Elina A.; Palgova, Lyudmila K.; Karev, Vadim E.; Marchenko, Natalya V. (International Journal of Psychosocial Rehabilitation, 2020)
Inflammatory bowel disease (IBD) and primary sclerosing cholangitis (PSC) are two separate diseases, with still unclear etiologies that continue to be investigated. Clinic manifestation of IBD-PSC is different from separate clinics of these diseases. A great portion of different scientific surveys witness of connection between IBD and PSC. Still, there is no enough data to perform a large randomized trial for imaging a clear picture of the IBD-PSC connection condition. Most prevalent is a combination between primary sclerosing cholangitis and ulcerative colitis. In our clinical case, we headed with a combination of primary sclerosing cholangitis and stomach form of Crohn’s disease (CD). The following clinical survey showed a rare case of primary sclerosing cholangitis with stomach’s Crohn’s disease combination, which was complicated by difficulties in diagnostic and correct treatment tactic selection. We tracked our patient from the beginning of first gastrointestinal symptoms in 2006 when gastric ulcer was revealed and 2014 when chronic gastric ulcer was diagnosed towards 2017 when our department visiting a patient was diagnosed rare gastric Crohn’s disease form and primary sclerosing cholangitis with ulterior colitis development in 2019. Further clinical examinations of similar clinical cases will confirm or deny out the assumption of a connection between gastric Crohn’s disease and primary sclerosing cholangitis.